1988
DOI: 10.1093/oxfordjournals.aje.a115007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Gallstone Disease in a General Population of Okinawa, Japan

Abstract: A total of 2,584 healthy residents in the Yaeyama District of Okinawa, Japan, were investigated in 1984 to determine the prevalence of gallstone disease and its associated factors. Diagnosis of gallstone disease was assessed by real-time ultrasonography. For participants over 20 years of age, obesity index and serum levels of total cholesterol and triglycerides were measured. Overall prevalence of gallstone disease was 3.2%. Prevalence increased with age from 0% under 19 years of age to 11.4% over 70 years of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
4
2

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(66 citation statements)
references
References 0 publications
5
55
4
2
Order By: Relevance
“…Epidemiological data have revealed that in the general population, the overall prevalence range of gallstones is 3.29%-14.85% (10)(11)(12)(13), and the overall prevalence range of NAFLD is 14%-40%. The pooled prevalence of GD in the NAFLD group in the present meta-analysis was 17%, which is higher than in the general population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological data have revealed that in the general population, the overall prevalence range of gallstones is 3.29%-14.85% (10)(11)(12)(13), and the overall prevalence range of NAFLD is 14%-40%. The pooled prevalence of GD in the NAFLD group in the present meta-analysis was 17%, which is higher than in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…The overall prevalence of gallstones is approximately 3.29%-14.85% in the general population (10)(11)(12)(13). Increased age, female sex, obesity, metabolic syndrome, hypertriglyceridemia, diabetes and insulin resistance are major risk factors for gallstones (10,14).…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, the suggestion that changing lifestyles and industrialization are probable causes of excess gallstone disease is to be discouraged as despite the economic dominance of Japan, gallstone prevalence there remained low [49]. A larger scale, perhaps nationwide, preferably population-based study will be needed to confirm our findings and to further assess possible genetic and/or environmental factors as possible causes for the formation of gallstones in Saudi females at a young age.…”
Section: Annals Of Saudi Medicine Vol 12 No 4; 1992mentioning
confidence: 67%
“…In the present study, the prevalence of synchronous gallstones was 4% in the nonresectable group and 5.5% in those undergoing surgical resection, showing no significant difference. The prevalence of gallstones in the general middleage population in Japan is about 5% (18) and increases to about 10% in the elderly (19). These results indicate that the prevalence of gallstones after esophagectomy may be low compared with that after gastrectomy, and may be almost the same compared with that of the general population.…”
Section: Discussionmentioning
confidence: 88%